IDENTIFIKASI BAKTERI LAUT SECARA MOLEKULER DARI OBJEK WISATA PUSAT LAUT KABUPATEN DONGGALA SULAWESI TENGAH - Ifandi, Slamet; Febriana Iffaf, Astri (Universitas Cokroaminoto Palopo, 2025)
Research in marine areas related to the potential of marine bacteria in Indonesia has been widely conducted. Information on bacterial research originating from the waters of Central Sulawesi, especially Donggala Regency, is still very rare and limited to observations of isolation and characterization. Therefore, a more accurate identification method is needed, namely using molecular. Molecular identification is considered more accurate when compared to other identification methods. This study aims to identify marine bacteria molecularly through the 16S rRNA gene. The method used in this study is experimental with a descriptive approach. The results of the molecular identification of bacterial isolates showed that isolate PS4 had the closest kinship level to Pseudomonas stutzeri. Isolate PS5 has a kinship with Bacillus megaterium and isolate PS6 has the closest kinship to Pseudomonas aeruginosa. All levels of kinship with those obtained were 100% percent identity.